Enarrationes in Psalmos 61–70 - Augustinus,Müller, Hildegund (De Gruyter, 2020)
Augustine’s commentaries on Psalm 61-70 are mostly based on sermons. In this edition, a special emphasis was laid on the adequate presentation of Augustine’s expressive and nuanced oral style. Each Enarratio is accompanied by an introduction, in which the known facts on time, date and liturgical circumstances are presented, as well as a precisely reconstructed version of the text of Augustine’s Psalter(s)
10.1515/9783110674675
Keywords: Exegese; Lateinische Philologie; Psalmen; Psalms; critical edition; exegesis; RELIGION / Christian Theology / History